(untitled) (Publicatio UEPG: Ciências Sociais Aplicadas, 2023)
The systemic approach in Restorative Justice aims at a new vision for the treatment of conflicts within the scope of Criminal Justice, with the use of Systemic Law that is based on the Family Constellation method, where it is possible to visualize that countless conflicts experienced by the individual can to be in situations generated in the past, by the person himself and his ancestors, making it difficult to apply the laws in their interpretation. Observing systemic laws interferes in such a way that conflicts can be resolved in a way that brings greater peace to relationships and are resolved more quickly and effectively, aiming at mitigating recidivism. The present study seeks to clarify this application in the judiciary through restorative justice. The author seeks to demonstrate the impact of systemic restorative justice on the Brazilian criminal system, aiming at a less punitive solution to a reparative result, aiming at reducing recidivism. Keywords: Criminal Law. Systemic Law. Systemic laws. Family Constellation. Systemic Restorative Justice.